β1-Integrin plays a major role in resveratrol-mediated anti-invasion effects in the CRC microenvironment - Brockmueller, Aranka; Mueller, Anna-Lena; Shayan, Parviz; Shakibaei, Mehdi (Frontiers in Pharmacology, 2022)
Graphical Abstract